From Liberty to Belonging: Rethinking the Pain of Punishment - Coppola, Federica (Springer Nature, 2026)
This article offers a critical examination of penal pain in the context of carceral punishment. It draws upon empirical insights from criminology and social psychology to challenge the prevailing assumption that the deprivation of liberty constitutes the primary source of suffering in imprisonment. Instead, it argues that much of the suffering associated with incarceration arises from systematic threats to the human need to belong. On this basis, the article positions belonging not merely as a core human need but as a fundamental right that warrants meaningful protection within custodial settings. It further contends that recognizing the centrality of belonging in the penal context can inform sentencing practices and recalibrate the standards of “humane” imprisonment to better safeguard the social needs of system-impacted individuals. Ultimately, the article advances belonging as an additional conceptual framework for bridging the gap between theoretical models of punishment and the lived realities of incarceration, particularly in light of the criminal justice system’s professed commitment to upholding the dignity of those subject to its authority.
Keywords: 56 Ciencias Jurídicas y Derecho; ODS 16 - Paz, justicia e instituciones sólidas; Punishment; Prison; Social pain; Belonging; Lived experience